Kresno Website: Development of BIPA Speaking Materials for Intermediate Level - Arif Fadillah; Nia Budiana; Machrus Abadi (Future Science, 2024)
This study aims to develop a media website kresno.id, for learning the speaking skills of BIPA students at Brawijaya University. The development of the Kresno.id website is based on learning to speak, which is still limited to textbooks as teaching materials and WhatsApp as a medium for practicing speaking online. However, the ability to speak has a vital role in the success of learning. In addition, the Kresno. id website media combines cultural elements. This research is a development research using the adapted Borg and Gall model. The resulting product is a Kresno.id website, which includes general website information, instructions for use, reasons for choosing the Kresno website, materials, dictionaries, speaking exercises, text-related information, video viewing, developer addresses, developer social media, and contacts. The data in this study were obtained from interviews with BIPA teachers, validation test results, and product trial results. The results of this study show (1) media expert validation gets a percentage of 99.16% with a perfect category, (2) material expert validation gets a percentage of 91% with a perfect category, and (3) linguist validation gets 96.15% with a perfect category. Good, (4) the final validation of expert practitioners obtained 85.66% in the perfect category. Based on the validation of the kresno.id website, it can be tested in a limited and broadway. The results of the wide trial show an average percentage of 88.36% with a perfect category. Implementing the Kresno.id website yielded an average score of 92 during the extensive trial.